Multilateralising Regionalism Strengthening Transparency Disciplines in Trade - Lejárraga, Iza (OECD Publishing, 2013)
Countries embarking on trade negotiations are not only seeking increased market access, but also, reduced market opacity. This study distils the most progressive practices for promoting regulatory transparency in over one hundred regional trade agreements (RTAs) concluded by OECD and large emerging economies over the last decade. While there is a lively discussion on strengthening transparency in the World Trade Organization (WTO), scant attention has been paid to the evolution of corresponding disciplines in RTAs. And yet, this study finds that RTAs can be credited for introducing instruments that not only deepen existing multilateral transparency commitments ("WTO-plus"), but expand them to new areas that do not have precedents in WTO agreements ("WTO-beyond"). In particular, the paper illuminates a number of options that may be useful for policy-makers to consider in their efforts to reinforce transparency and predictability in international trade policy. Most of the transparency mechanisms identified are being applied on a non-discriminatory basis, since they are often non-excludable and non-exhaustible. The implication is that, although WTO-plus transparency measures may be de jure preferential by virtue of being inscribed in an RTA, they are de facto being extended on a most-favoured nation (MFN) basis. Moreover, there is a considerable level of homogeneity in WTO-plus transparency provisions across a critical mass of RTAs, which may facilitate convergence and adoption at the multilateral level
Keywords: Trade